Neologisms in contemporary feminisms: For a redefinition of feminist linguistic activism - Océane Foubert (Glad!)
Feminist Linguistic Activism (FLA) encompasses more than just gender-fair language. In order to counter the androcentric nature of language, feminists have also coined new terms to highlight women’s experiences and forms of oppression. This approach, known as the disruptive approach, has been defined as the coinage of neologisms that emphasise women’s subordination and men’s domination. Contemporary feminisms have also introduced neologisms such as himpathy and misogynoir. However, as with the neologisms of the 1970s, little attention has been paid to the more recent ones. This study aims to shed light on these neologisms in FLA literature and answer the question: to what extent do the neologisms from contemporary feminisms redefine FLA? Based on a collection of neologisms in a crowdsourced dictionary, it is found that only a small portion of these neologisms align with the initial definition. By asking who are the women in this definition, most show the importance of naming for oneself rather than for others.